Secure fault-tolerant code for cloud storage - Peng-xu TAN; Yue CHEN; Ju-long LAN; Hong-yong JIA (Tongxin xuebao)
A secure regenerating code,called SRCS was proposed to solve the security problem during the process of the fault-tolerant of storage systems,especially the storage system in an extremely open environment such as cloud computing and cloud storage.SRCS achieves the security of the encoding matrix in the regenerating code using the threshold public-key encryption with low redundancy and high efficiency.It is proven that SRCS is secure in the semi-adaptive model using decisional BDHE assumption.